Media Ilmiah Teknologi Pangan (Scientific Journal of Food Technology) - Media Pangan (Master Program of Food Science and Technology, Faculty of Agricultural Technology, Udayana University, 2023)
The Front Matter of MITP, V.10 N.01, March 2023.